Modern trends in development of elite and youth ski jumping take-off technique - Zakharov, G. G.; Belyova, A. N.; Novikova, N. B.; Adodin, N. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the dynamics of angular characteristics of take-off variations in the ski jumping of the leaders of international competitions versus the Russian elite and junior ski jumpers in the major events of 2015 through 2020.